Enhancing the Cooling Effectiveness Utilizing a Tapered Fin Having Capsule-Shaped Cross-Sectional Area Numerically Simulated Using Finite Difference Method - Pratama, Nico Ndaru; Setyahandana, Budi; Purwadianto, Doddy; Dyaksa, Gilang Argya; Winarbawa, Heryoga; Seen, Michael; Rines, Rines; Mardikus, Stefan; Kusbandono, Wibowo; Lukiyanto, Y.B (International Journal of Applied Sciences and Smart Technologies, 2025)
This paper reports the results of our research on improving the cooling of an engine using fins. This problem is important to discuss because various parts of the world have utilized machining technology. When the engine operates, it produces heat. This heat reduces the efficiency of the engine's performance. In this problem, we developed a tapered fin method with a capsule cross-section to enhance cooling performance. The fin consists of two different materials that are perfectly joined. In this paper, the fin analysis is performed using the explicit finite difference numerical method. This method simulates the heat distribution on the fins. The results of our research include temperature distribution, heat flow rate, efficiency, and fin effectiveness in unsteady-state conditions with variations in material composition. The highest heat flow rate, fin efficiency, and fin effectiveness were achieved with a fin material composition of copper and aluminum, yielding an efficiency value of 0.89 and an effectiveness of 20.7. Our research results offer potential for the industry to design fins for innovative applications.